2012
DOI: 10.1089/neu.2011.2123
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Mild Lateral Fluid Percussion Brain Injury in the Rat Causes Cumulative Long-Term Behavioral Impairments, Neuroinflammation, and Cortical Loss in an Animal Model of Repeated Concussion

Abstract: There is growing evidence that repeated brain concussion can result in cumulative and long-term behavioral symptoms, neuropathological changes, and neurodegeneration. Little is known about the factors and mechanisms that contribute to these effects. The current study addresses the need to investigate and better understand the effects of repeated concussion through the development of an animal model. Male Long-Evans rats received 1, 3, or 5 mild lateral fluid percussion injuries or sham injuries spaced 5 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
161
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(180 citation statements)
references
References 65 publications
19
161
0
Order By: Relevance
“…Although there is some preliminary human evidence that adolescents may experience worse mTBI outcomes than young adults (see Semple et al, 2015),44 many of the changes in the current study are similar to those observed in adult rats given repeated mTBI. For example, adult male rats administered repeated mild fluid percussion injuries had cumulative and persisting cognitive deficits, motor abnormalities, anxiety‐like behavior, and depression 45, 46. Although we are unaware of any studies that have directly compared the effects of repeated mTBIs at different ages in rats, it should be noted that age‐specific changes do occur after more severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is some preliminary human evidence that adolescents may experience worse mTBI outcomes than young adults (see Semple et al, 2015),44 many of the changes in the current study are similar to those observed in adult rats given repeated mTBI. For example, adult male rats administered repeated mild fluid percussion injuries had cumulative and persisting cognitive deficits, motor abnormalities, anxiety‐like behavior, and depression 45, 46. Although we are unaware of any studies that have directly compared the effects of repeated mTBIs at different ages in rats, it should be noted that age‐specific changes do occur after more severe TBI.…”
Section: Discussionmentioning
confidence: 99%
“…The view that recovery might be at least partly achieved by such compensatory mechanisms, rather than full return to baseline condition 48 is supported by several reports suggesting cumulative effects of repeated concussions. [49][50][51][52] …”
Section: Tallus Et Almentioning
confidence: 99%
“…2,3 It is hypothesized that the first mTBI places the brain in a vulnerable state that is more susceptible to damage from subsequent injuries. [4][5][6] However, the nature of the changes produced by a single mTBI remains insufficiently characterized.…”
Section: Introductionmentioning
confidence: 99%